The impact of the Paramisi phenomenon in Torajan culture on the weakening of the religiosity and economic life of Catholics in Simbuang-Mammpak - Patrio Tandiangga; I Made Markus Suma; Frans Fandy Palinoan; Arwin Dama; Riwandi Riwandi (Universitas Muhammadiyah Malang, 2025)
The funeral rituals of the Toraja people frequently include a practice known as paramisi, commonly referred to as cockfighting. This study examines the impact of the paramisi phenomenon within Toraja culture on the religious lives of its adherents. Furthermore, this research aims to assess the contemporary relevance of maintaining paramisi tradition in daily life. A qualitative research methodology was employed, which is suitable for investigating the conditions of natural objects. Data were collected through interviews with 10 informants, including community leaders, government officials, religious leaders, individuals actively engaged in cockfighting, those who had ceased participation, and family members of the congregation or cockfighting participants. The findings of this study reveal that cockfighting exerts a negative influence on community life, particularly concerning the economic aspects and spiritual well-being of the congregation (religiosity). It is anticipated that this study will contribute to the discourse among congregational and pastoral practitioners by fostering awareness of the adverse effects associated with cockfighting. Dalam proses pemakaman orang Toraja kerap dilaksanakan apa yang disebut dengan paramisi. Paramisi lebih sering dikenal secara umum dengan istilah sabung ayam. Penelitian ini bertujuan untuk mengetahui dampak dari fenomena Paramisi dalam budaya Toraja terhadap kehidupan religiusitas umat beragama. Selain itu penelitian ini juga ingin melihat sejauh mana tradisi paramisi masih relevan untuk dipertahankan dalam kehidupan seghari-hari. Penelitian ini akan menggunakan metode kualitatif. Metode kualitatif merupakan metode penelitian yang digunakan untuk meneliti pada kondisi obyek yang alamiah. Pengumpulan data dilakukan dengan cara wawancara kepada 10 orang narasumber. Narasumber terdisi dari tokoh masyarakat, pemerintah, tokoh agama, masyarakat yang aktif melakukan sabung ayam, masyarakat yang sudah tidak aktif sabung ayam, dan anggota keluarga dari umat atau pelaku sabung ayam. Hasil penelitian ini menunjukkan bahwa sabung ayam memberikan dampak yang negatif terhadap kehidupan masyarakat khususnya dalam asepk ekonomi maupun aspek kehidupan rohani umat (religiusitas). Penelitian ini diharapkan mampu memberikan sumbang pemikiriran bagi para umat dan pelaku pastoral, agar segera memiliki kesadaran akan dampak negatif dari sabung ayam.